Pengaruh Pemberian Pupuk Kompos terhadap Pertumbuhan Rumput Setaria (Setaria sphacelata. S) - Maria Imelda Kolo; Stefanus Sio (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2020)
This research has been carried out in the experimental garden of the Faculty of Agriculture, University of Timor, Urban Village Sasi, Kefamenanu City District, North Central Timor Regency. This Study lasted for 2 months From June – July 2019. This study aimed to determine the effect of compost fertilizer on the growth of Setaria grass (Setaria sphacelata. S), the research design used was RAL with 4 treatments and 4 replications. The treatments consisted of R0 : control, R1 : compost 125g / planting hole, R2 : 159g / planting hole, R3 : 375g /palting hole, the results of the study show that composting can increase growth and yield of plants, the highest plant height is found in R3 : 45,07 cm, the highest number of tillers is in R3 4,85, the highest number of leaves is in R3 ; 21,22 strands, fresh weight production is in R3 = 1000 g and dry weight production is in R3 : 35,69 g. The conclusion from the results of this study is that the provision of compost 375 g/ planting hole can increase the growth of setaria grass better and the provision of compost fertilizer is very good to be applied to the cultivation of setaria grass (Setaria sphacelata. S).